The impact of psoriasis on the clinical characteristics, disease burden and treatment patterns of peripheral spondyloarthritis. (22nd April 2022) - Izci Duran, Tugba; Torgutalp, Murat; Rios Rodriguez, Valeria; Proft, Fabian; López-Medina, Clementina; Dougados, Maxime; Poddubnyy, Denis
Abstract: Objectives: To evaluate the clinical characteristics, disease burden, and treatment patterns of peripheral spondyloarthritis (pSpA) patients with and without psoriasis using data from the ASAS-perSpA study. Methods: We included 433 patients who had a diagnosis of pSpA according to the rheumatologist's diagnosis from the ASAS-PerSpA study. The presence of a personal history of psoriasis was defined as the presence of signs of psoriasis at physical examination or the presence of psoriatic nail dystrophy, including onycholysis, pitting and hyperkeratosis, or a history of psoriasis diagnosed by a physician. Clinical characteristics, patient-reported outcomes and treatment pattern were compared between subgroups with and without psoriasis. Results: A total of 83 patients (19.2%) had a personal history of psoriasis. Patients with psoriasis were older (48.4 vs 43.2 years) and had a longer diagnostic delay (7.4 vs 3.5 years), a higher frequency of dactylitis (36.1 vs 20.0%) and enthesitis (65.1 vs 55.4%) than patients without psoriasis. A longer diagnostic delay (odds ratio [OR] = 1.06 [95% CI 1.01, 1.11]), lower odds for HLA-B27 positivity (OR = 0.31 [95% CI 0.15, 0.65]) and higher odds for enthesitis (OR = 2.39 [95% CI 1.16, 4.93]) were associated with the presence of psoriasis in a multivariable regression analysis. While patient-reported outcomes were comparable between groups, a higher use of biologic DMARDs was observed in patients with vs without psoriasis. Conclusion: The presence of psoriasis has an impact on clinical characteristics of pSpA. pSpA patients without psoriasis were less frequently treated with biologic DMARDs despite similar disease burden as compared with patients with psoriasis.